2015
DOI: 10.3892/ol.2015.3068
|View full text |Cite
|
Sign up to set email alerts
|

miR-218 inhibits the proliferation of glioma U87 cells through the inactivation of the CDK6/cyclin D1/p21Cip1/Waf1 pathway

Abstract: Abstract. Malignant gliomas are the most common and deadly primary brain tumors in adults and the high proliferative ability of these cells is one of the most important causes of the poor prognosis of this cancer. Suppressing the proliferation of malignant gliomas cells by altering effector molecules can significantly improve the prognosis of a patient. microRNAs (miRNAs) are small non-coding RNA molecules ~22 nucleotides in length that are able to function as oncogenes or tumor suppressors in human cancer. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
(31 reference statements)
1
17
0
Order By: Relevance
“…Numerous studies have demonstrated that miR-218 can be regarded as a tumor suppressor in a number of cancer types, including esophageal carcinoma (17), hepatocellular carcinoma (18), lung carcinoma (19), pancreatic cancer (20), glioma (21) and prostate cancer (22). It has been reported that miR-218 can also be regarded as a tumor suppressor in osteosarcoma (11), which is consistent with the present data.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies have demonstrated that miR-218 can be regarded as a tumor suppressor in a number of cancer types, including esophageal carcinoma (17), hepatocellular carcinoma (18), lung carcinoma (19), pancreatic cancer (20), glioma (21) and prostate cancer (22). It has been reported that miR-218 can also be regarded as a tumor suppressor in osteosarcoma (11), which is consistent with the present data.…”
Section: Discussionsupporting
confidence: 91%
“…As a cell cycle arrest protein, p21 is able to protect cells from apoptosis and induces G 1 phase cell cycle arrest by inactivating cyclin A/ cyclin dependent kinase (CDK)2 complexes (33). Furthermore, ectopic expression of miR-218 was demonstrated to induce G 1 /S checkpoint arrest, which resulted in the inhibition of glioma cell proliferation through the upregulation of p21 (34). Therefore, the expression of PCNA, cyclin E, cyclin A1, cyclin A2 and p21 were investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhao et al reported that miR-3188 regulates nasopharyngeal carcinoma proliferation through a FOXO1-modulated positive feedback loop with mTOR-p-PI3K/AKT-c-JUN (24); moreover, a study from He and colleagues showed that miR-16 targeting fibroblast growth factor 2 inhibited NPC cell proliferation through PI3K/AKT and MAPK signaling pathways (25). Notably, numerous studies indicated that miRNAs regulated cancer cell proliferation via directly targeting single or several cell cycle-related genes, including cyclin D, cyclin E and cyclin-dependent kinase (CDK), which promoted the unlimited proliferation of cancer cells (26,27). Therefore, the above results imply that dysregulation of miRNAs promote the NPC cells proliferation, which contributes to the progression and recurrence of NPC.…”
Section: Introductionmentioning
confidence: 99%